Correction: Non-GABA sleep medications, suvorexant as risk factors for falls: Case-control and case-crossover study. - Yoshiki Ishibashi (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pone.0238723.].